Personalized initial screening age for colorectal cancer in individuals at average risk - Chen, Xuechen; Heisser, Thomas; Cardoso, Rafael; Hoffmeister, Michael; Brenner, Hermann (JAMA network open, 2023)
Colorectal cancer (CRC) risk varies widely in the population at average risk without a family history, but there are no established routines for translating this variation into personalized starting ages of screening.To illustrate derivation of risk-adapted starting ages of CRC screening based on the concept of risk advancement period (RAP) using sex and a polygenic risk score (PRS) as an example.This cohort study included participants in the UK Biobank study recruited in England, Wales, and Scotland between March 13, 2006, and October 1, 2010. Participants were aged 40 to 69 years, with no previous bowel cancer screening and no family history of CRC. Follow-up of cancer data was completed February 29, 2020, for England and Wales and January 31, 2021, for Scotland. The censoring date for death data was September 30, 2021, for England and Wales and October 31, 2021, for Scotland.Data on age, sex, and family history were collected at the baseline interview. A PRS was calculated based on 139 CRC-related risk loci.Hazard ratios (HRs) of sex and PRS with CRC risk and mortality were estimated using Cox proportional hazards regression models and were translated to RAPs to quantify how many years of age earlier or later men and individuals in higher or lower PRS deciles would reach risks comparable with those of the reference group (ie, women or those in the 5th and 6th PRS deciles).Among 242779 participants (median age, 55 [IQR, 48-61] years; 55.7% women), 2714 incident CRC cases were identified during a median follow-up of 11.2 (IQR, 10.5-11.8) years and 758 deaths during a median follow-up of 12.8 (IQR, 12.0-13.4) years. The HRs of CRC risk were 1.57 (95% CI, 1.46-1.70) for men vs women and ranged from 0.51 (95% CI, 0.41-0.62) to 2.29 (95% CI, 2.01-2.62) across PRS deciles compared with the reference. The RAPs were 5.6 (95% CI, 4.6-6.6) years for men vs women and ranged from −8.4 (95% CI, −11.0 to −5.9) to 10.3 (95% CI, 8.5-12.1) years across PRS deciles compared with the reference deciles. Risk-adapted starting ages of screening would vary by 24 years between men in the highest PRS decile and women in the lowest PRS decile. Similar results were obtained regarding CRC mortality.In this large cohort study including women and men at average risk of CRC, risk-adapted starting ages of screening strongly varied by sex and a PRS. The RAP concept could easily accommodate additional factors for defining personalized starting ages of screening.
Gesehen am 01.12.2023